A New Look at Cultivar Preference in Hoplocampa testudinea (Hymenoptera: Tenthredinidae) on Apple in the Annapolis Valley of Nova Scotia, Canada - Suzanne Blatt; Kim Hiltz (Insects, 2021)
(1) Background: The European apple sawfly, Hoplocampa testudinea Klug (Hymenoptera: Tenthredinidae), can be an economically important pest in eastern Canada and shows preference for apple cultivars in Nova Scotia, Canada. We hypothesized that this preference could be due to oviposition by female H. testudinea (preference-performance hypothesis) during the bloom period or differential larval survival during development due to fruitlet physicochemical properties. (2) Methods: Fifteen commercial and experimental apple (Malusdomestica Borkh.; Rosaceae) cultivars located at the Kentville Research and Development Centre (Kentville, Nova Scotia) were chosen and examined for H. testudinea oviposition, larval performance during fruitlet development, fruitlet physicochemical properties and damage assessment at harvest from 2016–2019, inclusive. (3) Results: H. testudinea showed significant cultivar preference during oviposition, during development and at harvest, but the ranking of these cultivars was not the same throughout the season. Total impact by H. testudinea was consistent for most cultivars over multiple years of the study. (4) Conclusion: Correlation of oviposition with damage provided weak evidence for the preference-performance hypothesis. We propose that this relationship is weak due to differential survival of larvae during development.